2014
DOI: 10.2147/ibpc.s40248
|View full text |Cite
|
Sign up to set email alerts
|

Which thiazide to choose as add-on therapy for hypertension?

Abstract: Combined therapy is required in the majority of patients with hypertension to achieve blood pressure (BP) targets. Although different antihypertensive drugs can be combined, not all combinations are equally effective and safe. In this context, the combination of a renin angiotensin system inhibitor with a diuretic, usually a thiazide, particularly hydrochlorothiazide (HCTZ) or thiazide-like diuretics, such as chlorthalidone or indapamide, is recommended. However, not all diuretics are equal. Although HCTZ, chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
0
3
0
2
Order By: Relevance
“…Confusion has been seen in other settings and countries when there is conflicting advice, and should be avoided if possible (53). Treatment guidelines should be reviewed to reflect for instance the growing evidence showing superiority of chlorthalidone over hydrochlorthiazedine (54,55), although others are less sure (56). We will be monitoring this in the future.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Confusion has been seen in other settings and countries when there is conflicting advice, and should be avoided if possible (53). Treatment guidelines should be reviewed to reflect for instance the growing evidence showing superiority of chlorthalidone over hydrochlorthiazedine (54,55), although others are less sure (56). We will be monitoring this in the future.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, as with beta-blockers, not all diuretics have the same effect on glucose homeostasis. Thus, it seems that chlorthalidone may have a more favorable metabolic profile compared with other thiazide or thiazide-like diuretics [ 45 , 62 ]. In addition, other study showed that whereas amiloride and hydrochlorothiazide reduced BP levels to a similar extent, treatment with hydrochlorothiazide was associated with an increase of glucose levels after a 2-hour oral glucose tolerance test, but not with amiloride [ 63 ].…”
Section: Role Of Calcium Channel Blockers In the Treatment Of Patientmentioning
confidence: 99%
“…Наряду с этим, индапамид вызывает регресс гипертрофии левого желудочка, улучшает качество жизни пациентов с АГ. В отличие от других тиазидных диуретиков индапамид оказывает минимальное влияние на уровни общего холе-стерина и триглицеридов [13].…”
Section: артериальная гипертензияunclassified